Methods for Determination of Absolute Configurations of Chiral Diols by THENA Ester and NMR Shift Difference - Dolsophon, Kulvadee; Soponpong, Jakapun; Kornsakulkarn, Jittra; Thongpanchang, Chawanee; Thongpanchang, Tienthong (Synlett, 2022)
Determination of the absolute configuration of chiral secondary diols by chiral derivatizing agent (CDA) and NMR shift difference is of great challenge due to the complication from the interference of the aromatic anisotropic shielding effect of the two CDAs in close proximity. In this work, tetrahydro-1,4-epoxynaphthalene-1-carboxylic acid (THENA) was introduced as an alternative CDA for diols to overcome such complexity. Since the deshielding effect of THENA is weaker than the shielding effect of other CDAs, THENA would allow the direct analysis of the chemical shift difference in determining the absolute configuration of the chiral diols. In addition, an analytical method based on Riguera’s model could also be used to confirm the assignment. With a good agreement between the assigned configuration based on both analytical models, the absolute configuration of the chiral diols could be assigned with reliability.
Keywords: absolute configuration; chiral derivatizing agent; diols; NMR shift difference; natural products; stereochemistry; THENA